2021
DOI: 10.33073/pjm-2021-005
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Pathogenesis of Staphylococcus Bloodstream Infections in Humans: a Review

Abstract: Staphylococci are among the most frequent human microbiota components associated with the high level of bloodstream infection (BSI) episodes. In predisposed patients, there is a high risk of transformation of BSI episodes to sepsis. Both bacterial and host factors are crucial for the outcomes of BSI and sepsis. The highest rates of BSI episodes were reported in Africa, where these infections were up to twice as high as the European rates. However, there remains a great need to analyze African data for comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 91 publications
2
10
0
Order By: Relevance
“…The results found in this study corroborate studies developed in other health services in Brazil in which a higher frequency of positive samples of blood cultures by bacteria of the genus Staphylococcus was also observed, especially by coagulase-negative Staphylococcus, in addition to a higher occurrence of infections in sectors that treat patients in a higher state of severity (Perna et al, 2015;Ruschel et al, 2017;Dallacorte et al, 2016;Foletto et al, 2019).…”
Section: Methodssupporting
confidence: 89%
“…The results found in this study corroborate studies developed in other health services in Brazil in which a higher frequency of positive samples of blood cultures by bacteria of the genus Staphylococcus was also observed, especially by coagulase-negative Staphylococcus, in addition to a higher occurrence of infections in sectors that treat patients in a higher state of severity (Perna et al, 2015;Ruschel et al, 2017;Dallacorte et al, 2016;Foletto et al, 2019).…”
Section: Methodssupporting
confidence: 89%
“…Previous studies have reported that the increase of Bacteroidetes and the decrease of Firmicutes are beneficial to intestinal health [ 46 ]. Bacteroides are generally beneficial in the intestine, whereas Staphylococcus promotes infection [ 47 , 48 ]. Interestingly, Wang et al found that Bacteroides spp that positively correlated with the progress of colitis was significantly increased in the gut, which decreased in the Prunella vulgaris - (PVH-) treated dextran sulfate sodium- (DSS-) induced acute colitis rats [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus is a main causative agent of bone and joint infections in orthopedic medicine [1], and is a formidable Gram positive pathogen. S. aureus is also responsible for numerous other types of bacterial diseases including skin and soft tissue infections [2], sepsis [3], and respiratory illnesses [4]. In addition to the arsenal of virulence factors that S. aureus produces during infection [5], S. aureus also forms biofilms that resist both host defenses and chemical/antibiotic attack [5,6].…”
Section: Introductionmentioning
confidence: 99%